Сontribution to the knowledge of Parabelbella (Acari, Oribatida, Damaeidae): description of two new species from Russia and the U.S.A., redescription of P. inaequipes (Banks, 1947) and a key to known species - Ermilov, Sergey G.; Ryabinin, Nikolay A. (Zootaxa, 2020)
The genus Parabelbella (Oribatida, Damaeidae), with nine known species, is distributed in the Holarctic and Neotropical regions; of these, two new species from the Russian Far East and the U.S.A. are described on the basis of adult specimens. Parabelbella rusfareastensis sp. nov. differs from Parabelbella crenatosetosa Bulanova-Zachvatkina, 1967 by the smaller body size, the absence of propodolateral apophysis, direction of notogastral seta c1, and the mutual distance between notogastral setae c. Parabelbella pseudoinaequipes sp. nov. differs from Parabelbella inaequipes (Banks, 1947) by the presence of distinctly barbed notogastral setae la and lm and sparsely barbed setae c1, c2, lp, h3, shorter and thinner dorsal notogastral setae, anterior median ventral tubercle, and by distance between insertions of seta lm–lp. The redescription of P. inaequipes is presented, based on material from the U.S.A. The main morphological traits for this species are summarized. An identification key to known species of Parabelbella is provided.